Drivers of Sustainable Consumption – Life Satisfaction and the Concreteness of Sustainable Product Attributes in Advertising - Béatrice Martin; Christina Antoine Reh (Marketing Review St.Gallen, 2023)
To promote the sustainability of their products, marketers are rethinking their advertising. This study investigates the role of consumer life satisfaction and concrete messages in advertising. It shows that dissatisfied individuals attach higher importance to sustainable product attributes when they are presented in concrete terms, thus providing insights into the psychology of sustainable consumption.
Keywords: 650